Environmental and socio-economic impacts of community forestry and individual small-scale logging in Cameroon - Tsanga, R.; Cerutti, P.O.; Tabi Eckebil, P.P.; Essiane-Mendoula, E. (Routledge, 2022)
Community forests (CF) and individual small-scale logging (SML) have been promoted in the Cameroonian forest legal framework with several objectives: involving people in forest management, transferring some management rights, and improving local living conditions supported by natural resources. This chapter briefly presents the history of both CF and SML and their stated objectives. Through a brief assessment of the existing literature and available recent data, it compares the respective contribution of CF and SML to the principles of sustainable forest management. Findings indicate that both CF and SML have positive socio-economic impacts, though these are generally short-lived. Long-term impacts are mixed, with economic returns sustained by degradation of the resource base and largely captured downstream. From an environmental point of view, the complexity of the regulatory framework to establish CFs, their location in a ‘non-permanent forest domain’, and the lack of extension services supporting the local populations in implementation, in parallel with the rapidly increasing demand for wood on the domestic market, indicate that CFs also fail on many criteria of sustainable forest management.